The influence of Islamic spirituality in sustaining ethical consumer decision making - Mhd. Sarif, Suhaimi (2018)
Sustaining ethical consumer decision making is essential to assure ethical business environment. Collective efforts enable everyone contributes to ethical business environment. Besides rational-approach of ethical decision making, religious approach through Islamic spirituality provides inner strength for decision makers to be firm in decision making and implementation. Islamic spirituality includes integrity, sincere, transparent, and assertive. Thus, this situation leads to the objectives of the study to explore the effects of Islamic spirituality on having sustainable ethical consumer decision making framework. Effects are referring to influence with consistent impact on certain attitude, which is ethical consumer decision making. This study uses personal interview with ten (10) consumers to solicit their feedback on factors of Islamic spirituality influencing ethical consumer decision making on sustainable basis. The feedback from the informants pointed the effects of Islamic spirituality in terms of practices, behaviors, attitudes, and contexts. Informants argued that sustainable practice requires perpetual behavior with consistent attitudes in simulating environment. Islamic spirituality is not separated from physical practices. Nevertheless, the finding of this study is limited to the contexts of the 10 informants with rich feedback, which can be generalized at other places. Future studies should include many informants and to use case study method.